MAZHAB: KETERKUNGKUNGAN INTELEKTUAL ATAU KERANGKA METODOLOGIS (Dinamika Hukum Islam) - Nafiul Lubab; Novita Pancaningrum (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
Dynamic of Muslim life on earth is not cracked from the issue of the growing people phenomenon. In the fact, Muslims of the Prophet Muhammad era did not get obstacles in facing the reality of the problems. It happens because Prophet Muhammad’s companions always solve the problem based on Qur’an, hadith, or directly ask the Prophet (though they have different idea) so that the methodological problems to do ijtihad do not occur. However, after the Prophet’s death, the crucial issue of Muslims appears one by one. Ijtihad differs widely in solving the problem of how people get the shari’ah legality. Chronologically, the period after Prophet Muhammad’s death, his companions began to raise different schools of fiqh until the period tabi’in, tabi’in tabi’in and so on. On the other sides, whether the schools of fiqh are interpreted by Muslims as imitation to follow so that there’s no chance for thinking. This is so-called people’s captivity or by the existence of these schools of fiqh Muslims will read strategically as an instrument to analyze and overcome Muslim’s problem or more extremely Islam without schools of fiqh thought and Islamic arguments are built only based on the Qur’an and Sunah. Based on this case, the author wants to examine the schools of fiqh further in this paper.